(untitled) (Annals of Medical Research, 2024)
Aim: To compare the effects of C-MAC D-Blade and McGrath MAC X3 Blade videolaryngoscopes (VLs) during double lumen tube (DLT) insertion in one-lung ventilation (OLV) in patients who underwent chest surgery in terms of intubation durations, hemodynamic responses, and intubation-induced complications. Materials and Methods: Fifty patients aged 18−65 who were scheduled for OLV were included in this study. The patients were divided randomly into two groups: a Storz C-MAC D-Blade VL group (C-MAC group, n = 25) and a McGrath MAC X3 Blade VL group (McGrath group, n = 25). The results of a preoperative airway assessment, a number of intubation attempts and incidence of success at the first attempt, glottic view times, intubation times, Cormack−Lehane scores, percentage of glottic opening (POGO) scores, ease of intubation, comorbidities, hemodynamic responses, and intubation-related adverse events were recorded. Results: The demographic characteristics and comorbidities of both groups were similar. The intubation characteristics of both groups were similar in terms of Cormack−Lehane scores, thyromental and intergingival distances, and POGO scores. In the C-MAC group, the glottic view times (p = 0.001) and intubation times (p = 0.001) were significantly shorter than those in the McGrath group. As shown by ease of intubation scores, ease of intubation in the C-MAC group was significantly better than that in the McGrath group (p = 0.001). All the patients in the C-MAC group were intubated at the first attempt, without a statistically significant difference. The two groups were similar with respect to intubation-related complications and hemodynamic responses (mean arterial pressure and heart rate). Conclusion: We conclude that the C-MAC D-Blade VL is more beneficial for airway management due to shorter glottic view and intubation times, high success rates at the first attempt, and ease of intubation in patients intubated with a DLT in OLV.